Answering questions posed by health system stakeholders using linked administrative health data at the Institute for Clinical Evaluative Sciences (ICES). (2017) - Yates, Erika A.; Vermeulen, Marian J.; Saskin, Refik; Victor, Charles J.; Paprica, Alison P.; Schull, Michael J.
No abstract available